2020
DOI: 10.1093/femsec/fiaa007
|View full text |Cite
|
Sign up to set email alerts
|

Body site-specific microbiota reflect sex and age-class among wild spotted hyenas

Abstract: Host-associated microbial communities, henceforth ‘microbiota’, can affect the physiology and behavior of their hosts. In mammals, host ecological, social and environmental variables are associated with variation in microbial communities. Within individuals in a given mammalian species, the microbiota also partitions by body site. Here, we build on this work and sequence the bacterial 16S rRNA gene to profile the microbiota at six distinct body sites (ear, nasal and oral cavities, prepuce, rectum and anal scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 142 publications
1
14
0
Order By: Relevance
“…There are at least two possible explanations for the discrepancies. First, sex differences in gut composition might lead to sex differences in fecal glucocorticoid metabolites without affecting salivary cortisol (Goymann, 2012;Rojas et al, 2020). Second, juveniles sampled via saliva tended to be younger than juveniles sampled via feces in earlier studies (Greenberg, 2017), perhaps affecting the trends we found.…”
Section: Demographic Covariatesmentioning
confidence: 69%
“…There are at least two possible explanations for the discrepancies. First, sex differences in gut composition might lead to sex differences in fecal glucocorticoid metabolites without affecting salivary cortisol (Goymann, 2012;Rojas et al, 2020). Second, juveniles sampled via saliva tended to be younger than juveniles sampled via feces in earlier studies (Greenberg, 2017), perhaps affecting the trends we found.…”
Section: Demographic Covariatesmentioning
confidence: 69%
“…Collecting appropriate proportions of varying age classes for valid comparisons in wildlife studies presents challenges when relying on passive collection of stranded animals. Although not well studied, differences in age class-related resistance between harbor seals and porpoises may reflect differences in microbiome composition such as the nascent fecal biome of pups and calves compared to older animals as has been described in spotted hyenas (Crocutta crocutta) [59].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiomes, inclusive of intracellular and extracellular microorganisms, are often distinguishable across host body sites within species [ 14 20 ]. Within each site, they can act in a context-dependent manner as harmful, helpful, or harmless to hosts—with potentially integrated metabolisms and interacting gene products ( Fig 1 ) .…”
Section: Living and Evolving In A Microbial Worldmentioning
confidence: 99%